Service Quality Measurement and Consumer Perception about the Services of Banking Institutions - Purohit, H. C.; Pathardikar, Avinash D. (Indian Journal of Marketing, 2007)
Over the last few years, the increasing need to enhance income especially fee-based income, improve market share, improve quality of service and reduce cost of operations has forced most hanks to rethink and adopt varying business strategies and models. Key elements of strategies seen to be adopted by leading Indian banks include building a strong presence in India and international markets, customer-focused product innovation, financial resilience and a strong operating environment. Strong prudential and supervisory norms are requiring banks in India to conform to higher standards. As the Indian economy looks to integrate more into the global economy, the banking industry looks to keep pace. Key strategic elements: capital, consolidation and corporate governance are to be focused. The banking organizations need to make a time-to-time appraisal of their performance. The results of sales analysis, if indicate a sharp fall in the deposits, would be successful in identifying the reasons responsible for the same. If the competitive banks propose to offer a new service or a new scheme and the market test is to be conducted, the marketing research would make available the preferences and reactions of the prospects. If the old service or schemes are not getting a positive response, the marketing research would suggest ways to innovate the marketing resources. In this competitive era of global economy the efforts should be made to satisfy the users/consumers. If we succeed in satisfying the consumers/users, we also get a success in increasing the market share which makes the ways for establishing leadership. It is against this background that we make an advocacy in favour of innovating the marketing efforts which simplify our task of satisfying the users. Today the repute service generating organizations are making sincere efforts to practice the concept of total quality management. This makes it essential that the policy decision makers make multi-cornered efforts to have a new perception of quality. As consumer is the king in the market in case of any industry, so their perception towards the banks services should be measured and expectations about the services of their banks must be satisfied.The proposed study covers the issues related with the measurement of service quality and record responses of the bank customers about the services of the Nationalized Banks in India.